2016
DOI: 10.1017/cbo9781316536346
|View full text |Cite
|
Sign up to set email alerts
|

Women Warriors and Wartime Spies of China

Abstract: In this compelling new study, Louise Edwards explores the lives of some of China's most famous women warriors and wartime spies through history. Focusing on key figures including Hua Mulan, Zheng Pingru and Liu Hulan, this book examines the ways in which these extraordinary women have been commemorated through a range of cultural mediums including film, theatre, museums and textbooks. Whether perceived as heroes or anti-heroes, Edwards shows that both the popular and official presentation of these women and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…It is the militiawomen's femininity, their youth and beauty, that underscores the pervasiveness of military training and the readiness of the entire nation to defend the country-down to those groups within the population that according to more conventional notions of gender relations would be those to be defended. 38 It is not incidental that, according to one version of the story describing how Mao Zedong wrote his poem for Li Yuanhui, he added the most conventional and ubiquitous trope about armed women: "You young people should be courageous, you should not emulate Lin Daiyu [the tragic and frail heroine of Honglou meng (红楼梦 Dream of the red chamber)], but Hua Mulan and Mu Guiying." 39 The latter two legendary women warriors entered the army in their father's and husband's stead; Louise Edwards has shown that the literary figure of Hua Mulan actually worked to stabilize rather than disrupt the patriarchal system.…”
Section: The Militiawoman As Allegory Of Class and Nationmentioning
confidence: 99%
“…It is the militiawomen's femininity, their youth and beauty, that underscores the pervasiveness of military training and the readiness of the entire nation to defend the country-down to those groups within the population that according to more conventional notions of gender relations would be those to be defended. 38 It is not incidental that, according to one version of the story describing how Mao Zedong wrote his poem for Li Yuanhui, he added the most conventional and ubiquitous trope about armed women: "You young people should be courageous, you should not emulate Lin Daiyu [the tragic and frail heroine of Honglou meng (红楼梦 Dream of the red chamber)], but Hua Mulan and Mu Guiying." 39 The latter two legendary women warriors entered the army in their father's and husband's stead; Louise Edwards has shown that the literary figure of Hua Mulan actually worked to stabilize rather than disrupt the patriarchal system.…”
Section: The Militiawoman As Allegory Of Class and Nationmentioning
confidence: 99%
“…For studies on women warriors and sex spying during 1930s and 1940s China, especially concerning the conflicting calls for female fidelity and national service, seeEdwards (2016Edwards ( , 2020.…”
mentioning
confidence: 99%